Scopariadulcis (SDF7) endowed with glucose uptake properties on L6 myotubes compared insulin. - Joo, Ee Beh; Latip, Jalifah; Abdullah, Mohd Puad; Ismail, Amin; Hamid, Muhajir (Elsevier, 2010)

(untitled)
Aim of the study Insulin stimulates glucoseuptake and promotes the translocation of glucose transporter 4 (Glut 4) to the plasma membrane on L6myotubes. The aim of this study is to investigate affect of Scopariadulcis Linn water extracts on glucoseuptake activity and the Glut 4 translocation components (i.e., IRS-1, PI 3-kinase, PKB/Akt2, PKC and TC 10) in L6myotubescompared to insulin.